Evaluating the role of negative affect and negative interpretation biases in emotional eating behavior. Issue 7 (2nd June 2022) - Klein, Kelly M.; Fitzgerald, Elizabeth H.; Forney, Katherine Jean; Kennedy, Grace A.; Keel, Pamela K.
Abstract: Objective: The study of emotional eating, or (over)eating in response to emotions, may inform transdiagnostic interventions for eating pathology. Prior work has focused on the role of negative affect in promoting emotional eating. The present study sought to extend this work through examining the role of cognitive biases. Method: Women who self‐reported ( n  = 50) and did not self‐report ( n  = 40) emotional eating completed self‐report questionnaires of negative affect and negative interpretation biases, an implicit measure of cognitive bias, and a behavioral assay of emotional eating involving an ad lib test meal following a stress induction task. Results: The emotional eating group endorsed elevated trait negative affect, explicit shame biases, and implicit negative biases compared to controls. In addition, state negative affect increased after the stress induction task, and the emotional eating group endorsed greater state negative affect before and after the task and consumed more food following the stress induction. Only explicit cognitive shame biases demonstrated significant indirect effects in the association between group and food consumption. Specifically, elevated explicit shame biases were positively associated with amount of food consumed for the emotional eating group. Discussion: Future research should examine whether interventions that target cognitive biases related to shame reduce emotional eating. Public Significance: Individuals with emotional eating consumed more food than controls following a stress induction. Explicit shame cognitive biases were positively associated with amount of food consumed for the emotional eating group. Shame cogntiive biases may be fruitful targets for reducing emotional eating.